PERAN RELIGIOUS COPING SEBAGAI MODERATOR DARI JOB INSECURITY TERHADAP STRES KERJA PADA STAF AKADEMIK - Triantoro Safaria (HUMANITAS: Indonesian Psychological Journal, 2011)
Job stress is a main problem for modern organization. It has negativeeffect on employee, organization and productivity. Previous study foundthat job stress could create several problems and difficulties either on workperformance or employee’s health status. This study aims to examinerelationship between job insecurity and religious coping as moderatorvariable with job stress among university academic staffs. Moderatedregression analysis was used to analyze the data. One hundred and fifty-five academic staffs participated in this study. The result showed that jobinsecurity has significant effect on job stress. Meanwhile, religious copinghas significant effect on job stress by moderating the effect of job insecurity.Further discussion will be explained in this paper.